2001
DOI: 10.1080/15287390151126388
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF BENZENE EXPOSURE IN CHILDREN LIVING IN CAMPANIA (ITALY) BY URINARYtrans,trans-MUCONIC ACID ASSAY

Abstract: The urinary benzene metabolite trans,trans-muconic acid (MA) was determined in 144 children living in Campania (Italy): 92 from Naples (1,300,000 inhabitants), designated as an urban source, and compared to 52 from Pollica (300 inhabitants), considered a rural, background exposure for benzene. The children participating in the study were tested by an anonymous questionnaire about the possible sources of exposure to benzene. Quantifiable levels of MA were found in 63% of the urine samples analyzed. Setting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 30 publications
0
10
1
Order By: Relevance
“…Among them, urinary tt- MA is increasingly recognized as a reliable and relatively convenient biomarker [14], [15], [16]. The compound tt- MA is an open-ring (nonphenolic) metabolite of benzene [17].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, urinary tt- MA is increasingly recognized as a reliable and relatively convenient biomarker [14], [15], [16]. The compound tt- MA is an open-ring (nonphenolic) metabolite of benzene [17].…”
Section: Introductionmentioning
confidence: 99%
“…Weaver et al (1996) conducted a pilot study to evaluate the feasibility of using trans,trans-muconic acid (MA) as a biomarker for environmental benzene exposure in urban children. In a recent study conducted on 144 children living in Italy, Amodio-Cocchieri et al (2001) also used MA as a biomarker for environmental exposure. Measurements of benzene biomarkers, which can provide information on individual variation in absorption and 5 metabolism and, thus susceptibility to adverse health effects, appear to be useful in the case of benzene.…”
Section: Introductionmentioning
confidence: 99%
“…The mean or median urinary ttMA concentrations range from 30 µg/g creatinine to 300 µg/g creatinine among non-occupationally benzene exposed populations (Amodio-Cocchieri et al., 2001; Fustinoni et al., 2005b; Kim et al., 2006a; Melikian et al., 2002; Navasumrit et al., 2005; Pezzagno et al., 1999; Qu et al., 2000; Scherer et al., 1998; Waidyanatha et al., 2004; Weaver et al., 2000). Smoking habits significantly influence ttMA levels (Buratti et al., 1996; Fustinoni et al., 2005b; Ghittori et al., 1995, 1996; Lauwerys et al., 1994; Lee et al., 1993; Melikian et al., 1993, 1994; Ong et al., 1994; Ruppert et al., 1995, 1997).…”
Section: Biomarkers/analytical Methodologymentioning
confidence: 99%
“…On a group basis, urinary ttMA concentrations allow discrimination between smokers and non-smokers. Individuals living near or being in areas with high traffic density can have slightly higher urinary ttMA levels (Amodio-Cocchieri et al., 2001; Scherer et al., 1995; Weaver et al., 1996). In contrast, other researchers found that traffic density did not result in significant differences in urinary levels of ttMA among children from urban and rural areas (Barbieri et al .…”
Section: Biomarkers/analytical Methodologymentioning
confidence: 99%